THE EFFECTIVENESS OF QUANTUM TEACHING BASED ON DIGITAL MEDIA ON SELF-EFFICIENCY - Henni Fitriani; Agus Muliaman; Khaira Usrati; Mirnawati Mirnawati (Prosiding Seminar Nasional Biotik, 2022)
This study aims to describe the effectiveness of digital media-based quantum teaching on students' self-efficacy in the learning process in terms of gender. This research is based on the lack of use of learning models and media, causing low self-efficacy owned by students. The purpose of this study was to determine the effectiveness quantum teaching of digital media-basedThis study uses a quasi-experimental with a quantitative approach. The research design used was a pretest-posttest control group design. The population in this study amounted to 180 students, with a sample of 60 students including 30 female students and 30 male students. Sampling in this study using purposive sampling technique.data analysis technique used a nonparametric test (Run Test). The results of data analysis show a sig value of 0.000, this value represents that there is an influence of the digital media-based quantum teaching model on students' self-efficacy.